O advento da subjetividade autônoma no movimento da leitura dialógica dos escritos de Michel Foucault - Silva, Leandro Prates (2022)
The present research aims to reactivate the power of life in young people, problematize the notion of self-care, according to Michel Foucault, with the hope of contributing to thinking about the teaching of philosophy as a place where one learns to care and where one learns to make one's own life. a masterpiece. Therefore, at first, we sought, through clippings, to understand the context of the formation of philosophy as a curricular component in the history of education in Brazil until its implementation in the curriculum, with the aim of understanding its meaning throughout the Brazilian educational process so that so we can understand the current condition established in Law nº 13.415/2017 and have a teaching of philosophy focused on self-care. In the second moment, we sought to know and to present the genesis of self-care and its practices, so that, finally, in the third moment, we could, through dialogical gatherings, establish an interaction between the teaching of philosophy and the theory of self-care. itself, by Foucault and, thus, produce some essays and philosophical experiences in the classroom that allow detachment, a transformation of the self, that is, a modification of the ways of acting in the world and relating to it, which does not simply designate a turning attention to oneself, but, from that same attention, above all, a change. Thus, we believe that this challenge will allow us to think about the problems of the current moment that we face with the teaching of philosophy and, above all, that we face in life. And make these problems the impulse to exist and resist to socioeconomic, educational, moral, cultural impositions and, thus, create a new subject, a new teaching, a new school, consequently, a new world.